KAJIAN EFEKTIVITAS KOLAM DETENSI KUNINGAN UGM UNTUK PENGURANGAN BANJIR KALI BELIK - , ARUM RATRI HAPSARI; , Prof. Ir. Joko Sujono, M.Eng., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rapid changes of land use around University of Gadjah Mada and Yogyakarta State University causing the catchment area of Belik river switching function so the ability of soil to absorb water decreases, direct runoff increases and flooding triggered. The effect of frequent flooding can harm nearby residents, therefore, a good strategy is needed to prevent the flooding. In this study, flood control is done by using a detention pool. Detention pool is chosen as an alternative because beside its functions to control the flood discharge, it can also be used for other purposes. The purpose of this final project is to determine the inflow through the detention pool and the effectiveness of the detention pool based on the outflow discharge with four variation of outlet structures. Rainfall distribution that will be used to determine the rainfall design obtained by proccessing the rainfall data during five years observation. Rainfall data is taken from BPTP Sleman rainfall recording station. Transformation of the rainfall is done by using a synthetic unit hydrograph Nakayasu while flood routing is done by the HEC - HMS program using the outlet structures routing . From this study, the detention pool inlet discharge is 9,3 m 3 /s. The most effective outlet structure is a combination of 3 meters length and 1,4 high broad crested spillway with three orifice. The effectiveness of the detention pool with those outlet structure is 7,8 % and the lag time is 1 hour.